The role of autologous conchal cartilage in ossiculoplasty during canal wall down mastoidectomy - Jalisatgi, Roshan; Garag, Santosh S.; J. S., Arunkumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: This study was done to evaluate the hearing outcome in patients undergoing ossiculoplasty using autograft cartilage in canal wall down surgery for cholesteatoma. Methods: This is a retrospective study. This was conducted in a tertiary care hospital from January 2011 to January 2014. This study included 54 patients who underwent canal wall down mastoidectomy with tympanoplasty during this period. Results: Preoperative and postoperative ABG for short columella were 23.13 dB (±11.21) and 12.66 dB (±8.92) respectively. Preoperative and post-operative ABG for long columella were 36.96 dB (±6.73) and 24.77 dB (±10.36) respectively. This is statistically significant. Conclusions: The use of autologous cartilage in ossiculoplasty during canal wall down mastoidectomy gives excellent hearing gain. It is also a cheaper option which is financially feasible in developing countries.